Perlindungan Hukum Kreditur atas Debitur Wanprestasi Perjanjian Perdamaian yang Telah Dihomologasi dalam Proses Penundaan Kewajiban Pembayaran Utang : Studi Putusan Nomor 375/Pdt.Sus-KPU/2022/PN.Niaga.Jkt.Pst - Anina Syahwita Pane; Mahmul Siregar; Hasim Purba (Jurnal Hukum Lex Generalis, 2026)
A homologated peace agreement in the PKPU process is not automatically void when the debtor defaults, but rather grants creditors the right to file for cancellation. The case of PT Multi Karya Utama Abadi demonstrates that executing cancellation is difficult due to assets being bound by the Foundation's Building Use Rights and cooperation agreements. Legal protection for creditors can be pursued through actio pauliana, cancellation of homologation, bankruptcy and consumer protection channels both through litigation and non-litigation via BPSK. However, the position of concurrent creditors remains weak in the distribution of bankruptcy assets. Policy reformulation is needed to provide priority to property buyers and strengthen pre-construction regulations to protect creditors acting in good faith.